Application of Sanctions for Return Action to Parents to Children Criminals - Kamri, Andi Khaedhir (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
One form of sanction regulated in the law is the act of returning to parents. This action aims to return children to their family environment so that they can be fostered and directed properly. In Article 59 of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, it is stated that the government and State institutions have an obligation and responsibility to protect children by providing special protection to children, especially to children who are dealing with the law, both children in conflict with the law and children as victims of criminal acts. This research uses the Normative Juridical research method. This method is carried out by conducting an assessment and analyzing laws and regulations. The results of the study were that the effectiveness of the sanctions for return actions was also influenced by the socio-economic conditions of the family. Many families experience economic difficulties so that they are unable to provide good education and supervision to children. In conclusion, the application of sanctions for returning actions to parents against children who commit criminal acts has a strong legal basis, but still faces various challenges in practice. The effectiveness of these sanctions is greatly influenced by the role of parents, family socioeconomic conditions, and existing social stigma. Therefore, a comprehensive approach is needed to improve the success of child rehabilitation.